2021
DOI: 10.1002/pip.3467
|View full text |Cite
|
Sign up to set email alerts
|

LeTID mitigation via an adapted firing process in p‐type PERC cells from SMART cast‐monocrystalline, Czochralski and high‐performance multicrystalline silicon

Abstract: In this work, we analyse passivated emitter and rear cells (PERC), based on wafers made from seed manipulation for artificially controlled defects technique (SMART) monocrystalline silicon, magnetically grown and conventional Czochralski (mCz and Cz) silicon, and high‐performance multicrystalline (hpm) silicon. All wafers were processed identically except for the hpm wafers, which received an acidic texture instead of random pyramids. The energy conversion efficiency η of the SMART cells of 21.4 % is similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The extent of LeTID can be manipulated by different factors, like the peak temperature of the firing step [15], [24], the cooling ramp of the firing step [12], [25], different preannealing steps [26], [27], [28], but also sample properties like the composition of the silicon nitride layer [7], [29], [30], interlayers such as aluminum oxide (Al 2 O 3 ) [31], [32], or the thickness of a sample [13], [33]. It was shown that the initial hydrogen concentration correlates with the peak firing temperature [34], besides other factors like the composition of the hydrogen-containing dielectric surface layers [35], or interlayers such as Al 2 O 3 [32], [36].…”
Section: A Light-and Elevated-temperature-induced Degradationmentioning
confidence: 99%
“…The extent of LeTID can be manipulated by different factors, like the peak temperature of the firing step [15], [24], the cooling ramp of the firing step [12], [25], different preannealing steps [26], [27], [28], but also sample properties like the composition of the silicon nitride layer [7], [29], [30], interlayers such as aluminum oxide (Al 2 O 3 ) [31], [32], or the thickness of a sample [13], [33]. It was shown that the initial hydrogen concentration correlates with the peak firing temperature [34], besides other factors like the composition of the hydrogen-containing dielectric surface layers [35], or interlayers such as Al 2 O 3 [32], [36].…”
Section: A Light-and Elevated-temperature-induced Degradationmentioning
confidence: 99%
“…Both, the set-peak temperature (i.e., 810 °C) and the band velocity (6 m min −1 ) of the firing furnace were lower in the present study, than in our previous study (850 °C, 6.8 m min −1 ). Whereas the lower firing peak temperature would result in less hydrogen diffusing into the silicon bulk, a slower cooling ramp has also been shown to have significant impact on the extent of degradation 29 . Another difference is the sample structure with poly-Si on the back of our lifetime sample instead of a symmetrical stack of AlO x and SiN y .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of PERC, LID and LETID were mainly analyzed by using small size cells. 24,[28][29][30][31][32][33] Comparing with these reports and outdoor exposed cell and module data will give us a better knowledge and understanding. Outdoor exposure tests of these four kinds of PERC modules will also be continued in the future.…”
Section: Sk1036-5mentioning
confidence: 99%